On the Mode of Vibration of a Layered Flat Topped Conical Hill of Deccan Trap Type and the Stresses Generated in Each Layer Part II - Datta, Jayasri; Mitra, Sachinath (Defence Science Journal, 2014)
In this paper the mode of vibration and the stresses in each layer of a 3-layered flat-topped conical hill have been calculated; and the solution is presented in terms of Bessel function. The condition of fracturing is also specified.